MULTI-PHOTONS TRAPPING STABILITY WITHIN A FIBER BRAGG GRATING FOR QUANTUM SENSOR USE - ', Saktioto (Komunikasi Fisika Indonesia, 2014)
We propose an interesting result of the trapped multi photons distribution within a fiber Bragg grating. Thetrapped photons are confined by the potential well, which introduce the motion of photons in a fiber Bragg gratingaffected by multi perturbations. The external perturbations are defined as series of nonlinear parametric in terms ofpotential energy. This investigation is developed by using the nonlinear couple mode equations and under Braggresonance condition where the initial frequency of the light, ? 0 is the same value as the Bragg frequency, ? B . Theresults show that the higher perturbation series represents the potential well is much indifferent of equilibrium. Inapplications, the perturbation can cause the trapped photons instability which introduces the escape photons from thepotential well. The applications such as entangled photon source and quantum sensors can be performed.